A Geometrical Approach to Giffen Behavior: The Epstein and Spiegel Utility Function Revisited. (16th July 2017) - Fujimoto, Masaki
Abstract : Weber ( The Manchester School, Vol. 69 (2001), No. 6, pp. 616–622) has asserted that if we treat the production function of Epstein and Spiegel ( The Manchester School, Vol. 68 (2000), No. 5, pp. 503–515) as a utility function, then an inferior good exhibits Giffen behavior at certain prices and income levels. This paper shows that it is not correct. Furthermore, we develop a geometrical method (i) to identify a region in a consumption set where Giffen behavior appears, (ii) to show that Giffen behavior can be categorized into two types: 'subsistence‐driven' and 'satiation‐driven', and (iii) to present a new class of Giffen utility functions.